Deposition and characterization of CuInSe2 films for solar cells using an optimized chemical route - Berruet, Mariana (2011)
CuInSe2 (CISe) thin films have been deposited on glass using successive ionic layer adsorption and reaction (SILAR). The as-deposited films are treated at 400 °C in argon atmosphere and etched in KCN solution to remove detrimental secondary phases. The preparation and temperature of the precursor solutions, the duration of the reaction cycles and the duration of the annealing stage have been optimized. The films have been characterized employing grazing incident X-ray diffraction, Raman spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive scanning spectroscopy. Relevant semiconductor parameters have been calculated. Photoelectrochemical tests confirm p-type conduction. The films are crystalline and the stoichiometry can be improved by renewing the precursor solution after completing half of the cycles, annealing for 90 min and later etching in KCN. The quality of the material seems to be promising for application in solar cell devices.